Controlling draw resonance during extrusion film casting of nanoclay filled linear low-density polyethylene: an experimental study and numerical linear stability analysis - Rokade, Dhammaraj; Chougale, Sanket; Patil, Prashant; Bhattacharjee, Tanushree; Gawande, Dnyaneshwar; Pol, Harshawardhan; Dhadwal, Renu (Journal of Plastic Film & Sheeting, 2021)
Commercially important extrusion film casting (EFC) processes for manufacturing plastic films or sheets are hampered by several instabilities that severely limits their productivity. In this research we focussed on one important instability: the draw resonance that occurs during the EFC process mainly under extensional flow conditions. Draw resonance is the sustained periodic oscillations in the film dimensions, notably film width and thickness, when the process operates beyond a critical draw ratio (CDR). In this research our goal was to reduce this draw resonance instability by incorporating well dispersed nanoclay fillers in a base polymeric resin (such as a linear low density polyethylene - LLDPE) to determine how these nanocomposite (NC) formulations can prevent or reduce the draw resonance defect. EFC experiments were conducted on the base resin and on the NC formulations under non-isothermal conditions to determine the onset of the draw resonance experimentally. Conventional linear stability analysis was performed to determine the onset of the draw resonance defect numerically. Numerical predictions for the onset of draw resonance were in qualitative agreement with our experimental data. Our results showed that incorporating appropriate nanoclay concentrations in a base polymeric resin indeed enhanced the EFC process stability for those polymer formulations and thus can have important economic implications for processors.
Keywords: Draw resonance; extensional strain hardening; Extrusion; Film; hydrodynamic interactions; Nanoclay; Nanocomposites; Polyethylene; Rheology; stability